Penggunaan Biochar dan Tinggi Muka Air pada Umur Satu Bulan setelah Tanam terhadap Pertumbuhan dan Hasil Tanaman Bawang Merah - Susilawati Susilawati; Irmawati Irmawati; Sri Sukarmi; Astuti Kurnianingsih; Ade Mutia (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2019)
Susilawati S, Irmawati I, Sukarmi S, Kurnianingsih A, Mutia A. 2019. The application of biochar and water table at one month after planting on growth and yield of shallot.Â Jurnal Lahan Suboptimal: Journal of Suboptimal Lands. 8(2):202-212.Â The success of onion self-sufficiency is the arrangement and growth of production centers that are not only concentrated in Java. The research aimed to evaluate the effect of biochar application and water table treatment on growth and yield of shallot plant. The research was conducted in Experimental Farm of Agriculture Faculty, Sriwijaya University at 2019. Materials used consisted of shallot bulb of Bima Brebes variety, oil palm shells biochar, paper bag, and plastic bag. While the tools used were hoe, gauge, pH meter, basin, scale, and oven. Factorial Randomized Block Design was used with two factors and three replicates. The first factor was biochar dosages consisting of P1 (51 g/plant) and P2 (102 g/plant) and the second factor was soil water table consisting of T0 (no water table treatment), T1 (10 cm of water table below soil surface), T2 (15 cm of water table below soil surface) and T3 (30 cm of water table below soil surface). The observed parameters included plant height, leaf number, tiller number, total bulb fresh weight, bulb fresh weight, bulb dry weight and root length. Results showed that the application of biochar and water table treatment statistically affected the growth and yield of shallot plant. The effect on both growth and yield parameters were obtained from the combination of P2T3. Correlation was found between plant height and leaf number, total bulb fresh weight and bulb fresh weight.